2015
DOI: 10.1001/jamainternmed.2015.2829
|View full text |Cite
|
Sign up to set email alerts
|

The Strength of Association Between Surrogate End Points and Survival in Oncology

Abstract: The strength of association between surrogate end points and survival in oncology is important to understand because surrogate end points are frequently used in oncology clinical trials, supporting US Food and Drug Administration approvals and National Comprehensive Cancer Network guideline recommendations. OBJECTIVE To identify and evaluate trial-level meta-analyses of randomized clinical trials quantifying the association between a surrogate end point and overall survival in medical oncology. Trial-level cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
287
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 317 publications
(305 citation statements)
references
References 102 publications
2
287
1
6
Order By: Relevance
“…106 The review found that all validation studies used only a subset of the available trials and that the evidence supporting the use of surrogate outcomes in cancer trials is limited. The results are summarised in Table 3.…”
Section: Surrogate Outcomes In Oncologymentioning
confidence: 99%
“…106 The review found that all validation studies used only a subset of the available trials and that the evidence supporting the use of surrogate outcomes in cancer trials is limited. The results are summarised in Table 3.…”
Section: Surrogate Outcomes In Oncologymentioning
confidence: 99%
“…Although the goal of cancer treatment is to improve the quantity and quality of life,1 2 3 clinical trials designed to gain regulatory approval for new drugs often evaluate indirect or “surrogate” measures of drug efficacy. These endpoints show that an agent has biological activity, but they are not reliable surrogates for improved survival4 5 6 7 8 9 10 11 or quality of life4 6 11 12 13 in all settings, and two recent systematic reviews suggest that the strength of association between surrogates in cancer clinical trials and life extension is generally low 814 Moreover, there is growing concern that the benefits offered by many new treatments for cancer—often discussed and promoted as “breakthroughs”15 16 17 18—are marginal and might not be clinically meaningful to patients, despite rapidly escalating costs 19…”
Section: Introductionmentioning
confidence: 99%
“…The use of PFS, and similar measures other than OS, are not reliable surrogates for OS in general (24,25) (23) and specifically in noncurative settings (22). The usefulness of PFS as a surrogate for OS may depend, in metastatic or advanced cases, on cancer type.…”
Section: Evaluation Of Methods To Measure and Value Outcomes: Survivalmentioning
confidence: 99%